Pre- and in-hospital delays in the use of thrombolytic therapy for patients with acute ischemic stroke in rural and urban Egypt - Nasreldein, Ahmed; Walter, Silke; Mohamed, Khaled O.; Shehata, Ghaydaa Ahmed; Ghali, Azza A.; Dahshan, Ahmed; Faßbender, Klaus; Abd-Allah, Foad (Frontiers in Neurology, 2023)
Background Reducing pre- and in-hospital delays plays an important role in increasing the rate of intravenous thrombolysis (IVT) in patients with acute ischemic stroke. In Egypt, the IVT rate has increased steadily but is still far away from an ideal rate. Aim The study aimed to investigate the factors associated with pre- and in-hospital delays of IVT among patients with acute ischemic stroke coming from urban and rural communities. Methods This prospective, multicenter, observational cohort study was conducted from January 2018 to January 2019. Patients with acute ischemic stroke, who did not receive IVT, were included in the study. Patients were recruited from three large university stroke centers in Egypt, Assiut (south of Egypt), Tanta (north of Egypt), both serving urban and rural patients, and the University Hospital in Cairo (capital city), only serving an urban community. All participants underwent the National Institutes of Health Stroke Scale and full neurological assessment, urgent laboratory investigations, and computed tomography or magnetic resonance imaging to confirm the stroke diagnosis. The patients were subjected to a structured questionnaire that was designed to determine the parameters and time metrics for the pre- and in-hospital delays among patients from rural and urban regions. Results A total of 618 patients were included in the study, of which 364 patients (58.9%) lived in rural regions and 254 (41.1%) in urban regions. General demographic characteristics were similar between both groups. Approximately 73.3% of patients who arrived within the therapeutic time window were urban patients. The time from symptom onset till hospital arrival (onset to door time, ODT) was significantly longer among rural patients (738 ± 690 min) than urban patients (360 ± 342 min). Delayed onset to alarm time (OAT), initial misdiagnosis, and presentation to non-stroke-ready hospitals were the most common causes of pre-hospital delay and were significantly higher in rural patients. For patients arriving within the time window, the most common causes of in-hospital delays were prolonged laboratory investigations and imaging duration. Conclusion The limited availability of stroke-ready hospitals in rural Egypt leads to delays in stroke management, with subsequent treatment inequality of rural patients with acute stroke.